Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2016
DOI: 10.1016/j.devcel.2016.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Single-Cell Analysis Uncovers Clonal Acinar Cell Heterogeneity in the Adult Pancreas

Abstract: Acinar cells make up the majority of all cells in the pancreas, yet the source of new acinar cells during homeostasis remains unknown. Using multicolor lineage-tracing and organoid-formation assays, we identified the presence of a progenitor-like acinar cell subpopulation. These cells have long-term self-renewal capacity, albeit in a unipotent fashion. We further demonstrate that binuclear acinar cells are terminally differentiated acinar cells. Transcriptome analysis of single acinar cells revealed the existe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
79
1

Year Published

2017
2017
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 91 publications
(89 citation statements)
references
References 55 publications
2
79
1
Order By: Relevance
“…Progenitor Cell Signature and Early Differentiation Routes. Identification of a stem/progenitor cell population based solely on single-cell RNA sequencing (scRNA-seq) results is extremely difficult, particularly in tissues with rare such cells (36,37). Our FACS analysis indicated that Aldh1b1-expressing adult pancreatic cells represent just 0.5% of the cells in the adult organ.…”
Section: Aldh1b1-expressing Cells Are Necessary and Sufficient To Genmentioning
confidence: 89%
“…Progenitor Cell Signature and Early Differentiation Routes. Identification of a stem/progenitor cell population based solely on single-cell RNA sequencing (scRNA-seq) results is extremely difficult, particularly in tissues with rare such cells (36,37). Our FACS analysis indicated that Aldh1b1-expressing adult pancreatic cells represent just 0.5% of the cells in the adult organ.…”
Section: Aldh1b1-expressing Cells Are Necessary and Sufficient To Genmentioning
confidence: 89%
“…Short-lived progenitors are able to interconvert into stem-like cells after tissue damage,10, 23, 24 but it remains unclear whether such interconverted cells can develop into cancer. In organs such as pancreas and liver that do not frequently divide in the normal state, cancers may arise from more differentiated acinar and hepatocyte compartments, but recent evidence has suggested the existence within these compartments of specific facultative reserve stem-like cells, which preferentially may contribute to regeneration and give rise to cancer 25, 26, 27, 28, 29, 30. In any case, although it may be possible for non–stem cells to contribute to gastric regeneration and cancer, chronic inflammation associated with H pylori infection typically induces a regenerative and reparative response orchestrated by tissue resident stem cells, 31 which are activated and expand as part of an injury response, predisposing to the acquisition of genetic and epigenetic alterations (Figure 1).…”
mentioning
confidence: 99%
“…S3C, S3D), which can guide follow‐up experiments aimed at their isolation and characterization or validate previously reported associations. For example, it has been recently suggested that the TF STMN1 may act as a marker for progenitor‐like acinar cells . Our data supports this association given that its expression is highly correlated with acinar SSPCs in both pancreas datasets (Supporting Information Table S2; Fig.…”
Section: Resultsmentioning
confidence: 99%